Gingival mesenchymal stem cells: Biological properties and therapeutic applications - Yuanyuan Peng; Jacques Jaar; Simon D. Tran (Journal of Oral Biology and Craniofacial Research)
Our understanding of mesenchymal stem cells (MSCs) and their biological properties is steadily increasing, with more studies focusing on their therapeutic effects in the domains of immunology, tissue engineering and regenerative medicine. MSCs may be derived from tissues such as bone marrow, adipose, the umbilical cord, as well as from dental tissues (e.g., tooth germ, dental follicle, pulp tissue of exfoliated deciduous and permanent teeth, apical papilla, periodontal ligament, gingiva, and alveolar bone). Gingival mesenchymal stem cells (GMSCs) are non-hematopoietic adult stem cells isolated from the gingival lamina propria. When compared to MSCs purified from various dental and non-dental tissues, GMSCs are more abundant in source, relatively non-invasive to obtain, and genetically stable. In recent years, many studies have found that GMSCs possess the ability of self-renewal, multi-directional differentiation, and chemotaxis to inflammatory sites for immunity regulation. Their molecular and stem-cell properties make them highly suitable for both preclinical and clinical research. Extracellular vesicles (EVs) secreted by GMSCs are of key interest due to their ability to emulate the biological and therapeutic activity of GMSCs themselves. This paper will therefore review the current consensus on GMSCs, surveying their sources and isolation methods, their biological properties, and their therapeutic applications on inflammatory and immune-related diseases.